Madurese Islamic Preacher Perception about Early Matchmaking: Phenomenology Study in Pamekasan and Sumenep - Rifa'i, Mohammad (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
Madurese people are known as people who have a habit of pairing children at an early age, and some are even toddlers or babies still in the womb who have been booked for matchmaking. Early matchmaking in Madura is one of the causes of early marriage, and then it causes school dropouts. It needs attention from an influential person in the people, one of which is an Islamic preacher (da’i). The da’i perception of these social realities is important so that they can provide understanding to the Madurese people about the early matchmaking well. This study aims to answer: (1) how is Madura da’i perception about early matchmaking, and (2) how is the typology of Madura da’i on early matchmaking. To achieve these objectives, the author uses qualitative-field methods by collecting data through observation, interviews, and documentation. While for data analysis, the author uses the phenomenology theory. The result of this study: Madura da’i perceives early matchmaking as i'tikad (effort) that is an effort of parents who need to protect and worry about their children. Madura da’i also perceives that early matchmaking in Madura contains values of Islam; those are: (a) minimizing of approaching adultery, (b) inviting to follow sunnah, and (c) inviting to keep the family relationship. Besides that, there are two typologies of Madura da’i about early matchmaking; the first type is da’i who agrees to early matchmaking; the second type is da’i who disagrees with early matchmaking. They agree with early matchmaking as long as it does not end in early marriage. Otherwise, they do not agree if early matchmaking results in early marriages, and considering early marriages that do not lead to marriages sometimes causes hostility between families. The type of da’i who refuses is more suggesting that children are directed to the world of education first before being charged with the thinking of ​​matchmaking or marriage.